The Models of Islamic Syiar Approach by the Religious Counselors in Developing Religious Life in East Lampung Regency - Mubasit, Mubasit; Yanti, Fitri (FIKRAH, 2021)
East Lampung has been known as one of the Muslim bases in the Lampung Province. However, problems faced by Muslims in this region are quite complicated. Some of these issues are demoralization and the highly rate of criminalization. This study aims to describe and analyse the models of Islamic syiar approach applied by the religious counsellors in East Lampung. This research uses the descriptive qualitative method. The data is collected through in-depth interviews with the informants who have direct relation to the religious counselling activities. Besides, the direct observation is involved in analysing the activities of religious counsellors in doing their Islamic syiar. Moreover, surfing related documents to obtain relevant data with religious counselling activities such as rules, policies, and provisions is also entangled. Based on the conducted research, the religious counsellors in East Lampung use three approaches in performing their syiar in their community. They are the socio-cultural approach, the psychological approach and the political approach.